TrueNTH Sexual Recovery Intervention for couples coping with prostate cancer: Randomized controlled trial results. Issue 7 (5th January 2022) - Wittmann, Daniela; Mehta, Akanksha; Bober, Sharon L.; Zhu, Ziwei; Daignault‐Newton, Stephanie; Dunn, Rodney L.; Braun, Thomas M.; Carter, Caroline; Duby, Ashley; Northouse, Laurel L.; Koontz, Bridget F.; Glodé, L. Michael; et al.
Abstract : BACKGROUND: Despite significant sexual dysfunction and distress after localized prostate cancer treatment, patients typically receive only physiologic erectile dysfunction management. The authors performed a randomized controlled trial of an online intervention supporting couples' posttreatment recovery of sexual intimacy. METHODS: Patients treated with surgery, radiation, or combined radiation and androgen deprivation therapy who had partners were recruited and randomized to an online intervention or a control group. The intervention, tailored to treatment type and sexual orientation, comprised 6 modules addressing expectations for sexual and emotional sequelae of treatment, rehabilitation, and guidance toward sexual intimacy recovery. Couples, recruited from 6 sites nationally, completed validated measures at the baseline and 3 and 6 months after treatment. Primary outcome group differences were assessed with t tests for individual outcomes. RESULTS: Among 142 randomized couples, 105 patients (mostly surgery) and 87 partners completed the 6‐month survey; this reflected challenges with recruitment and attrition. There were no differences between the intervention and control arms in Patient‐Reported Outcomes Measurement Information System Global Satisfaction With Sex Life scores 6 months after treatment (the primary outcome). Three months after treatment, intervention patients and partners reported more engagement in penetrative and nonpenetrative sexual activities than controls. More than 73% of the intervention participants reported high or moderate satisfaction with module content; more than 85% would recommend the intervention to other couples. CONCLUSIONS: Online psychosexual support for couples can help couples to connect and experience sexual pleasure early after treatment despite patients' sexual dysfunction. Participants' high endorsement of the intervention reflects the importance of sexual health support to couples after prostate cancer treatment. LAY SUMMARY: This study tested a web‐based program supporting couples' sexual recovery of sexual intimacy after prostate cancer treatment. One hundred forty‐two couples were recruited and randomly assigned to the program (n = 60) or to a control group (n = 82). The program did not result in improvements in participants' satisfaction with their sex life 6 months after treatment, but couples in the intervention group engaged in sexual activity sooner after treatment than couples in the control group. Couples evaluated the program positively and would recommend it to others facing prostate cancer treatment. Abstract : Couples coping with prostate cancer participated in a randomized controlled trial of a sexual recovery support program. Although participants assigned to the intervention were not more satisfied with their sex life 6 months after treatment, they re‐engaged in sexual activity earlier than a control group and found the program beneficial.